Choice models for ecological solid waste management and strategic financing options for local governments - Naz, Antonio Crisanta Corinthia Navarro 1963- (2006)
The scope of government functions determines the scope of public administration. In most countries, including the Philippines, solid waste management (SWM) is a local government function as most SWM activities are considered public goods or services. The Philippines' Republic Act (RA) 9003 or the Ecological Solid Waste Management (ECOSWAM) Act mandates local government units (LGUs) to formulate and implment their 10-year ECOSWAM plans. This law sets very ambitious goals requiring huge financial investments, and their achievement will be a major challenge for all sectors of the society. Given limited resources and competing social services, many mayors believethat they will not be able to comply with the law's stringent requirements, such as the construction of sanitary landfills. Using a framework that covers public administration-public choice and governance, service delivery, people as clients and citizens and "voice" and "exit" options, this study aims to assist LGUs in examining strategic financing options in planning and implementing an ECOSWAM program that will enable them to comply with RA 9003. It determines the people's willingness-to-pay (WTP) for various ECOSWAM service options in terms of user fees, the potential revenues from these, the costs of the services and the funding gap. The funding gap is the amount that the LGUwill have to subsidize in order to provide the ECOSWAM services. The study also explores other financing options to address the funding gap and evaluates these using the governance elements of transparency, accountability, participation and predictability. The study contributes to the discipline of public administration by exploring inter-LGU cooperation (clustering) as a policy mechanism for solid waste management and byproposing a framework for the provision of public goods using the stated preference-choice modeling method. Choice modeling provides a systematic and participatory way of designing ECOSWAM user fees. The study site is the municipality of Tuba, province of Benguet, the neighbor of highly urbanized Baguio City. The people of Tuba ranked solid waste management as their number one environmental problem. However, they are willing to pay user fees that could cover only up to 35 percent of the maintenance and operating costs of ECOSWAM services. Among the options evaluated, the study recommends that the Tuba municipal government adoptScenario One, i.e. the option with the lowest funding gap and maintenance and operating costs and the highest cost recovery. This scenario is characterized by once a week collection of residual waste by municipal workers with a garbage truck. With this scenario, the Tuba municipal government will ahve to subsidize 65 percent of the yearly maintenance and operating costs (MOC) or about PhP2 million annually (25 percent of its development fund ). Without user fees, it will have to spend about 40 percent of its development fund or 15 percent of its total budget to finance the yearly MOC of the service. Including the capital costs of PhP10 million for the first year in the calculations will magnify the funding gap. Hence, there is a need for Tuba and similar LGUs, to explore additional financing options for ECOSWAM services. Other strategic financing options for ECOSWAM services. Other strategic financing options are those in the general budgetary appropriations and locally generated revenues and those from external sources requiring partnerships and special arrangements with civil society, the private sector and other government agencies. The first group includes the internal revenue allotment (IRA), the share of the proceeds from the development and utilization of the national wealth and other internally generated revenues like real property taxes (RPT), business taxes and other fees. These options are beset by issues regarding transparency, accountability and predictability. The second group of financing options includes co-production and sale of recyclables, subsidies and grants, Build-Operate-Transfer (BOT) schemes, joint ventures,contracting out, credit financing instruments and LGU clustering. In clustering, the overall cost of financing is spread among member LGUs, there is more flexibility due to a larger resource base and enhanced economies of scale and there is overall environment improvement.
Vita.
"March 2006."
Thesis (D. Public Administration)--University of the Philippines Diliman.
Keywords: Refuse and refuse disposal -- Philippines; Refuse and refuse disposal -- Law and legislation -- Philippines